(untitled) (Czech Journal of International Relations, 1995)
Charles W. Kegley, Jr., Gregory A. Raymond: Multipolar peace? Great Power Politics in the Twenty- first Century. St. Martin ’s Press, New York 1994, 278 stran, ISBN 0-312-10270-4.